Dietary Supplementation of Astragalus membranaceus Extract Affects Growth Performance, Antioxidant Capacity, Immune Response, and Energy Metabolism of Largemouth Bass (Micropterus salmoides) - Xuanshu He; Anqi Chen; Zhihong Liao; Jian Zhong; Anda Cheng; Xinghua Xue; Fuyuan Li; Mengdie Chen; Rong Yao; Wei Zhao; Jin Niu (Aquaculture Nutrition)
The present study investigated the effects of Astragalus membranaceus extract (AME) on growth performance, immune response, and energy metabolism of juvenile largemouth bass (Micropterus salmoides). Seven diets containing 0%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, and 0.6% AME (Con, AME0.1, AME0.2, AME0.3, AME0.4, AME0.5, and AME0.6 groups) were formulated and fed to M. salmoides for 8 weeks. Final body weight (FBW), feed intake (FI), weight gain (WG), and specific growth rate (SGR) were all significantly higher in AME0.4 group than in Con group (P<0.05). Feed conversion rate (FCR) was significantly improved in AME0.5 group compared with Con group (P<0.05). Whole-body crude protein contents were significantly increased in AME0.2 group (P<0.05). Whole-body crude lipid contents were significantly lower in AME0.2 and AME0.3 groups, while muscle lipid was upregulated by dietary AME (P<0.05). Hepatic malondialdehyde (MDA) contents were significantly lowered in AME0.3 and AME0.4 groups, and catalase (CAT) activities were significantly increased in AME0.1 and AME0.2 groups (P<0.05). Plasma aspartate aminotransferase (AST) level was significantly lowered in AME0.5, and AME0.6 groups, and alanine aminotransferase (ALT) level was lowered in AME0.5 groups (P<0.05). Plasma triglyceride was declined in AME0.6 group, and glucose was decreased by 0.3%−0.5% AME (P<0.05). Significantly higher hepatocyte diameter, lamina propria width, and submucosal layer thickness were recorded in AME0.6 groups, while the longest villi height was obtained in AME0.2 and AME0.3 groups (P<0.05). The mRNA expression levels of insulin-like growth factor 1 (igf1) revealed the growth-promoting effect of AME. The anti-inflammatory and antiapoptotic effects of AME were demonstrated by transcription levels of interleukin 8 (il-8), tumor necrosis factor-alpha (tnf-a), caspase, B-cell lymphoma-xl (Bcl-xl), bcl-2 associated x (Bax), and bcl-2-associated death protein (Bad). The transcription levels of lipid metabolism and gluconeogenesis related genes, including acetyl-CoA carboxylase alpha (acc1), fatty acid synthase (fasn), fatty acid binding protein 1 (fabp1), phosphoenolpyruvate carboxykinase 2 (pepck2), and glucose-6-phosphatase catalytic subunit 1a (g6pc), were reduced by AME treatment, while the levels of glycolysis-related genes, including glucokinase (gck) and pyruvate kinase (pk), were the highest in AME0.2 and AME0.3 groups (P<0.05). According to polynomial regression analysis of SGR, WG, FCR, whole-body crude lipid, MDA, and ALT, the optimal AME supplementation level was estimated to be 0.320%−0.429% of the diet. These results provided insights into the roles of AME in regulating immunity and metabolism, which highly indicated its potential as immunostimulants and metabolic regulators in diverse aquatic animals.